Perinatal Outcomes in HIV Positive Pregnant Women with Concomitant Sexually Transmitted Infections - Erin Burnett; Tammy L. Loucks; Michael Lindsay (Hindawi Limited, 2015)
Objective. To evaluate whether HIV infected pregnant women with concomitant sexually transmitted infection (STIs) are at increased risk of adverse perinatal and neonatal outcomes. Methods. We conducted a cohort study of HIV positive women who delivered at an inner-city hospital in Atlanta, Georgia, from 2003 to 2013. Demographics, presence of concomitant STIs, prenatal care information, and maternal and neonatal outcomes were collected. The outcomes examined were the association of the presence of concomitant STIs on the risk of preterm birth (PTB), postpartum hemorrhage, chorioamnionitis, preeclampsia, intrauterine growth restriction, small for gestational age, low Apgar scores, and neonatal intensive care admission. Multiple logistic regression was performed to adjust for potential confounders. Results. HIV positive pregnant women with concomitant STIs had an increased risk of spontaneous PTB (odds ratio (OR) 2.11, 95% confidence interval [CI] 1.12-3.97). After adjusting for a history of preterm birth, maternal age, and low CD4+ count at prenatal care entry the association between concomitant STIs and spontaneous PTB persisted (adjusted OR 1.96, 95% CI 1.01-3.78). Conclusions. HIV infected pregnant women with concomitant STIs relative to HIV positive pregnant women without a concomitant STI are at increased risk of spontaneous PTB.